The tourists gaze, the Cretans glance : archaeology and tourism on a Greek island - Duke, P. G. (Heritage, tourism, and community., 2007)
Using the sites on the island of Crete as an example, Duke first gives a brief overview of what is known of Cretan pre-history. He then explores how the sites have been observed by mostly European and American tourists from the early nineteenth century to the present. Duke is concerned with how guides and brochures filter the archeological information to the tourists and how a specific view of the past is being presented. He concludes by encouraging academics to engage the interest of the casual spectator by making information about the sites more accessible to non-specialists. A useful appendix has a list describing each site along with comments on its current condition.